2006
DOI: 10.21236/ada466169
|View full text |Cite
|
Sign up to set email alerts
|

Hot Flashes and Quality of Life Among Breast Cancer Patients

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…For example, there is ample evidence that inadequacy of information that patients receive about their disease and treatment options contribute to distress [22] and frustration [23], especially with regard to chronic disorders in childhood [24], and specifically to sickle-cell anaemia [25]. And employing quality-of-life parameters to study patients with Hodgkin's disease, it was found that a group treated and given information through bulletin for 3 months benefitted more in areas such as anxiety, depression, and life disruption than the group that received the standard care only [26]. Furthermore, lack of or inadequate information on a disorder can lead to a limitless variety of conceptions of causation, many of which are based on societal norms, ethos, superstitions, and religio-philosophical speculations, and may, in consequence, instigate interpersonal conflicts and lifestyle, which can potentially aggravate the effects of the focal disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is ample evidence that inadequacy of information that patients receive about their disease and treatment options contribute to distress [22] and frustration [23], especially with regard to chronic disorders in childhood [24], and specifically to sickle-cell anaemia [25]. And employing quality-of-life parameters to study patients with Hodgkin's disease, it was found that a group treated and given information through bulletin for 3 months benefitted more in areas such as anxiety, depression, and life disruption than the group that received the standard care only [26]. Furthermore, lack of or inadequate information on a disorder can lead to a limitless variety of conceptions of causation, many of which are based on societal norms, ethos, superstitions, and religio-philosophical speculations, and may, in consequence, instigate interpersonal conflicts and lifestyle, which can potentially aggravate the effects of the focal disorder.…”
Section: Discussionmentioning
confidence: 99%